PENGARUH PELAYANAN ADMINISTRASI, FASILITAS PENDIDIKAN DAN KOMPETENSI DOSEN TERHADAP KEPUASAN TARUNA POLITEKNIK TRANSPORTASI DARAT BALI (POLTRADA BALI) - Fajarwati, Fitria; Widanti, Ni Putu Tirka; Rahayu, Luh Riniti (LPPM Institut Pendidikan Nusantara Global, 2023)
Changes in people's mindsets about the importance of education have an impact on the increasing public interest in higher education. Higher education is considered to be a place that produces quality human resources. Increasingly fierce competition and the demands of society's needs for quality oriented toward the value of service users ultimately pressure organizations to be able to respond quickly. Facing this condition, the main thing that must be prioritized by universities is student satisfaction. This study aims to analyze the effect of administrative services, educational facilities, and lecturer competence on the satisfaction of Bali Land Transportation Polytechnic cadets. The number of samples used was 69 with the proportional sampling method. Data collection using a questionnaire The data analysis technique uses multiple linear regression analysis with the SmartPLS application. The results showed that administrative services, educational facilities, and lecturer competence had a positive and significant effect on the satisfaction of Bali Land Transportation Polytechnic cadets. Among the three influential independent variables, lecturer competence is the one that has the most influence on cadet satisfaction. The magnitude of the influence of independent variables on cadet satisfaction is 92.9%.